Cathepsin D inhibits AGEs-induced phenotypic transformation in vascular smooth muscle cells - Xingmin He; Songhao Tian; Lixia Bu; Xinna Zhao; Liqiang Zheng; Peigang Zhang; Renwei Guo; Mingfeng Ma (Scientific Reports)
Abstract This study investigates the role of Cathepsin D (CTSD) in diabetic vascular complications, particularly its impact on the phenotypic transformation of vascular smooth muscle cells (VSMCs) induced by advanced glycation end-products (AGEs), and explores its potential molecular mechanisms. CTSD was overexpressed in VSMCs using lentiviral vectors. Various methods, including CCK-8, immunofluorescence, SA-β-Gal staining, EdU assay, scratch assay, cell cycle analysis, and Western blotting, were employed to assess VSMC viability, proliferation, migration, senescence, and apoptosis. Additionally, transcriptomic and metabolomic analyses were conducted to investigate the molecular mechanisms underlying CTSD overexpression in VSMCs. AGEs treatment significantly inhibited CTSD expression in VSMCs, leading to reduced cell viability, enhanced proliferation and migration, increased senescence, and apoptosis. In contrast, overexpression of CTSD effectively inhibited AGEs-induced VSMCs proliferation, migration, senescence, and apoptosis. Combined transcriptomic and metabolomic analyses suggested that CTSD may affect VSMCs phenotypic transformation by inhibiting the glycolysis pathway. This study highlights the critical role of CTSD in the phenotypic transformation of VSMCs induced by AGEs and provides a new perspective for cardiovascular and cerebrovascular disease treatment. CTSD may emerge as a novel therapeutic target, though its specific molecular mechanisms and clinical application prospects in VSMCs phenotypic transformation require further investigation.